2004
DOI: 10.1161/01.cir.0000125741.88712.77
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Matrix Metalloproteinases Precedes Left Ventricular Remodeling in Hypertensive Heart Failure Rats

Abstract: Background-Matrix metalloproteinases (MMPs) are activated in dilated failing hearts, and angiotensin-converting enzyme (ACE) inhibition prevents left ventricular (LV) dilatation. However, it remains unclear whether activation of MMPs precedes or is secondary to LV remodeling, and an effect of ACE inhibition on MMPs is unknown. Methods and Results-Dahl salt-sensitive rats fed a high-salt diet from 8 weeks served as the hypertensive heart failure (HF) model. LV echo, histological study, measurement of mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
123
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 33 publications
11
123
2
2
Order By: Relevance
“…MMP 2 and 9 expression has been shown to be enhanced in pressure-overloaded cardiac hypertrophy in spontaneously hypertensive rats 3 and in Dahl salt-sensitive hypertensive rats. 4 Similar upregulation of MMPs has been also observed in human pressure-overloaded hearts because of aortic stenosis. 5 Recently, Heymans et al 6 have demonstrated that MMP 9 is involved in cardiac remodeling associated with hypertension.…”
supporting
confidence: 52%
“…MMP 2 and 9 expression has been shown to be enhanced in pressure-overloaded cardiac hypertrophy in spontaneously hypertensive rats 3 and in Dahl salt-sensitive hypertensive rats. 4 Similar upregulation of MMPs has been also observed in human pressure-overloaded hearts because of aortic stenosis. 5 Recently, Heymans et al 6 have demonstrated that MMP 9 is involved in cardiac remodeling associated with hypertension.…”
supporting
confidence: 52%
“…22,38 Our finding that EPL attenuated the increase in the MMP/TIMP ratio suggests that activation of mineralocorticoid receptors contributes to LV dilation in response to pressure overload. Despite LV dilation and an increase in the MMP/TIMP ratio, pressure overload was associated with increased interstitial and perivascular fibrosis, similar to that described by Rocha et al 11 and Sun et al 12 in rats subjected to chronic aldosterone infusion.…”
Section: Mineralocorticoid Receptors Mediate Interstitial Matrix Remomentioning
confidence: 87%
“…18 Mineralocorticoid receptors affect MMP activity, 10,21 and ACE inhibition suppresses MMP activation and prevents LV remodeling and dysfunction. 22 Thus, it is possible that aldosterone, acting via the mineralocorticoid receptors, is involved in mediating at least some of the cellular events observed in pressure overloadinduced myocardial failure.…”
mentioning
confidence: 99%
“…Portions of the RNA (2 mg) were subjected to reverse transcription (RT) with the use of random primers (Invitrogen, Carlsbad, CA, USA) and MuLV Reverse Transcriptase (Applied Biosystems, Foster City, CA, USA). The resulting complementary DNA was subjected to real-time PCR analysis with the use of a Prism 7700 Sequence Detector (Perkin-Elmer, Waltham, MA, USA), as previously described, 23 and with primers and TaqMan probes specific for atrial natriuretic peptide (ANP), 22 brain natriuretic peptide (BNP), 22 collagen type I 24 or type III, 24 angiotensin-converting enzyme (ACE), 22 the AT 1A 22 or AT 2 (5¢-CTGGCTGTGGCTGACTTACTC-3¢, 5¢-TTTGC ACATCACAGGTCCAAAG-3¢, and 5¢-TTGGCAACCCTTCCTCTCTGGGCA-3¢ as the forward primer, reverse primer and TaqMan probe, respectively; GenBank accession no. NM_022456) receptor, transforming growth factorb1 (TGF-b1) 22 or connective tissue growth factor (CTGF).…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%